Developing Professional Track towards Excellence in Academician’s Career Path - Jusoff, Kamaruzaman; Abu Samah, Siti Akmar (2009)
A career in academics entails far beyond teaching. Being an academician is a very good job. The freedom to think creatively and learn is priceless. In addition, an academician working towards a PhD goes through intellectually stimulating experience to be shared. Having a PhD is a must to all academics since the PhD experience is about much more than learning to do deep work in some technical area of expertise and being constructively critical. The key is to figure out ways of moving between the different facets of the job without becoming too crazy. In another aspect, an academician is most likely to encounter his role model in teaching, research and professional service environments which are the platforms in pursuit towards excellence. In fact, these are the three main areas within which a faculty member must demonstrate excellence and achievement in order to be promoted: research, teaching and professional service. Indeed, there may be an array of promotion tracks to fit such different career paths; these tracks may have different requirements for promotion. It is critically important that the junior faculty member be familiar with the requirements of their particular track early in the course of their career. He should find out the relevant requirements and expectations for promotion and be thinking about these matters from an early point in his career, rather than near the end when the promotion clock is ticking. This paper also focuses on the significance of getting a PhD, sharing good lessons and experiences during doctorate training, and giving practical job strategy description and academic solutions for a career roadmap towards excellence. The paper is written from the perspective of the authors, the former who has survived the fast track promotion process from a lecturer to a full professor at quite an early age of 39 years old and the latter having promoted to senior lecturer within five years of tenure. In the earlier section of this paper, it attempts to answer the questions: What is academic excellence and what defines "success" in academic excellence? What is required for promotion? The questions of where young and new academicians are heading to and how do they get there are also highlighted by laying out a general career roadmap academic excellence plan and importantly, present strategies to deal with the potential pitfalls and avoid some of the bumps in the road towards striving for academic excellence.